Pedaço de mim, ó metade arrancada de mim - a necropolítica na destituição do Poder Familiar - Alves, Maria Clara Matos Coelho (2024)
The dismission of Family Power removes the legal status of being father and mother from the parents and the child or adolescent is sent to the substitute family through adoption. This occurs when there is any threat or violation of their rights, if the possibilities of maintaining them in the family have been exhausted. The main objective of this research was to analyze the experiences, trajectories and emotional impasses of families deprived of Family Power. As secondary objectives, we intended to understand the monitoring work carried out with these family groups prior to and during the application of the protection measure, and after the sentence of dismissal; in addition to investigating the connection between vulnerability and the situations that culminated in the sheltering of destitute children and adolescents. To this end, anchored in the theoretical and methodological framework of Psychoanalysis, and with support from decolonial discussions, three different families were interviewed, in the figures of three women - sister, grandmother and mother - who had destitution as the outcome of their legal proceedings. The analysis was constructed with the preparation of a clinical diary based on the contacts established and the interviews carried out. The analysis items were grouped into three topics. The first addressed social and historical vulnerability, linked to issues of gender, class and race, which constitute the lives of these women and their ways of relating. In the second, the impasses involving women's reports on the actions of the Rights Guarantee Network, with accusations about impertinent and decontextualized actions, which aimed at their “adhesion” to the hegemonic and traditional way of life that was not possible and assimilable to them. The last item pointed out the suffering of the women resulting from the removal of their children and the vivid hope based on their return home, with precarious assimilation of the place of destitution that was sentenced to them. It is concluded that the narrative presents vulnerable women, in suffering, who demand attention, care and state assistance. It seems urgent that destitute families are included and considered so that some social visibility is guaranteed to them.